Parameterization of vertical profiles of governing microphysical parameters of shallow cumulus cloud ensembles using LES with bin microphysics - Khain, P; Heiblum, R; Blahak, U; Levi, Y; Muskatel, H; Vadislavsky, E; Altaratz, O; Koren, I; Dagan, G; Shpund, J; Khain, A (American Meteorological Society, 2018)
Shallow convection is a sub-grid process in cloud-resolving models for which their grid-box is larger than the size of small cumulus clouds (Cu). At the same time such Cu substantially affect radiation properties and thermodynamic parameters of the low atmosphere. The main microphysical parameters used for calculation of radiative properties of Cu in cloud resolving models are liquid water content (LWC), effective droplet radius and cloud fraction (CF). In this study, these parameters of fields of small warm Cu are calculated using large-eddy-simulations (LES) performed using the System for Atmospheric Modelling (SAM) with spectral bin microphysics. Despite the complexity of microphysical processes several fundamental properties of Cu were found: a) Despite the high variability of LWC and droplet concentration within clouds and between different clouds, the volume mean and effective radii per specific level vary only slightly; b) the values of effective radius are close to those forming during adiabatic ascent of air parcels from cloud base. These findings allow characterizing a cloud field by a specific vertical profiles of effective radius and of mean liquid water content, which can be calculated using the theoretical profile of adiabatic liquid water content and the droplet concentration at cloud base. Using the results of these LES, a simple parameterization of cloud-field averaged vertical profiles of effective radius and of liquid water content is proposed for different aerosol and thermodynamic conditions. These profiles can be used for calculation of radiation properties of Cu fields in large scale models. The role of adiabatic processes in the formation of microstructure of Cu is discussed.